Exploration of IL-32 (rs45499297) gene variations in EBV and MS patients - Aya R. Abood; Hula Y. Fadhil (Iraqi Journal of Pharmaceutical Sciences, 2024)
Interleukin-32 is a multifunctional cytokine linked to a variety of illnesses and inflammatory disorders, the central nervous system is affected by the chronic inflammatory disease known as multiple sclerosis (MS). Studies about found relationship between them are rare and inconclusive specially when MS patients with Epstein-Barr virus (EBV) positive. Recently, IL-32 identified increase and considers proinflammatory following EBV infection. A case-control study (79 MS patients and 108 controls) for the purpose of investigating T/C genotype of (rs45499297) in all participant then identify their role in MS and EBV patients by Restriction fragment length polymorphism (RFLP) technique. The results appeared that alleles and genotype (rs45499297) was no significant differences between MS patients and healthy controls, also between groups of expanded disability status scale in MS patients but with EBV infection was results appeared that allele C of( rs45499297) more effector in MS patients than controls. The mean of EBV load among multiple sclerosis patients according to sex, EDSS, and therapy line the results revealed that elevated viral load in male, EDSS ≥ 3.0 and in second line therapy compare to opposite groups. In conclusion, the study indicated the role of sex and MS activity in susceptibility to EBV reactivation. However, analysis of the IL-32 gene variants (rs45499297) may influence susceptibility to EBV along with MS associated with the allele C occurrence.